1989
DOI: 10.1080/15287398909531339
|View full text |Cite
|
Sign up to set email alerts
|

Medical evaluation of subjects with known body levels of 2,3,7,8,— tetrachlorodibenzo‐p‐dioxin

Abstract: Forty-one persons with a history of 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) exposure and measured adipose tissue TCDD levels were evaluated for potential health effects. No pattern of clinical abnormalities emerged related to TCDD levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
1
2

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 18 publications
5
32
1
2
Order By: Relevance
“…Changes in cell surface markers on T cells represent an apparently sensitive biomarker response to the effects of dioxin-like compounds in rodents and primates. Dioxin-like compounds can affect the primary immune response by changing the CD4/CD8 ratio or the ratio of other lymphocyte subpopulations (11,15,19,(38)(39)(40)(41). In the present study we found no associations between T-helper or Tsuppressor cells and the serum PCB/CALUX TEQ levels.…”
Section: Discussioncontrasting
confidence: 49%
“…Changes in cell surface markers on T cells represent an apparently sensitive biomarker response to the effects of dioxin-like compounds in rodents and primates. Dioxin-like compounds can affect the primary immune response by changing the CD4/CD8 ratio or the ratio of other lymphocyte subpopulations (11,15,19,(38)(39)(40)(41). In the present study we found no associations between T-helper or Tsuppressor cells and the serum PCB/CALUX TEQ levels.…”
Section: Discussioncontrasting
confidence: 49%
“…Other reports showed no alterations in immunoglobulin levels (Hoffman et al 1986;Jennings et al 1988;Jung et al 1998;Marth et al 1995;Michalek et al 1999;Nagayama et al 2001). A slight positive increase in IgG levels was found in two studies Webb et al 1989). However, these studies did not exclude subjects with concurrent medical conditions likely to increase circulating IgG levels (Ravel 1995).…”
Section: Discussionmentioning
confidence: 96%
“…One article reported total γ-globulin levels (Jansing and Korff 1994). Four studies described a decrease in immunoglobulin levels (Halperin et al 1998;Jansing and Korff 1994;Løvik et al 1996;Neubert et al 2000), and two studies reported increased IgG Webb et al 1989). Complement levels were determined in three studies, and only one of them included both C3 and C4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on community residents of Quail Run Mobile Home Park (Missouri residents, USA), environmentally exposed to contaminated industrial sludge, showed a significantly decreased percentage of lymphocytes expressing CD3þ, CD4þ, and CD2þ, but the mean numbers of each of the T-cell subsets was comparable between the groups (Hoffman et al 1986;Knutsen et al 1987). Subsequent studies (Evans et al 1988;Webb et al 1989) showed significant increases associated with higher concentrations of TCDD for IgG, %CD3þ, %CD8þ, number of T-cells, percentages of CD2þ, and CD4þ/Leu-8 position. Svensson et al (1994) indicated that high consumption of fatty fish from the Baltic Sea, contaminated with persistent organochlorine compounds, is associated with lower number of natural killer cells.…”
Section: 14mentioning
confidence: 99%